Charged Particle Motion and Electromagnetic Field in γ Spacetime - Carlos A. Benavides-Gallego; Ahmadjon Abdujabbarov; Daniele Malafarina; Bobomurat Ahmedov; Cosimo Bambi (My University, 2019)
We consider the electromagnetic field occurring in the background of a static, axially symmetric vacuum solution of Einstein’s field equations immersed in an external magnetic field. The solution, known as the γ metric (or Zipoy-Voorhees), is related to the Schwarzschild spacetime through a real positive parameter γ that describes its departure from spherical symmetry. We study the motion of charged and uncharged particles in this spacetime and particle collision in the vicinity of the singular surface and compare with the corresponding result for Schwarzschild. We show that there is a sharp contrast with the black hole case; in particular, in the prolate case (γ < 1) particle collision can occur with an arbitrarily high center of mass energy. This mechanism could in principle allow one to distinguish such a source from a black hole.
Keywords: γ metric; Zipoy–Voorhees metric; charged particle motion; electromagnetic field; high-energy collisions; Schwarzschild limit